Micropropagation and Synthetic Seed Formation in newly developed interspecific F1 hybrid of Cymbidium giganteum × Cymbidium elegans - Kohli, Sumegha (My University, 2016)
Cymbidium (family Orchidaecae) is a group of important ornamental plants used as pot plant and cut flower. The present work was focussed to study the micropropagation, maturation of PLBs and synthetic seed formation in newly developed F1 hybrid of Cymbidium giganteum × Cymbidium elegans. Multiplication of Cymbidium cultures was done using PLBs on MS basal media supplemented with 2.5μM BAP. Maturation of PLBs was carried out to achieve their efficient conversion into plantlets. Maturation was attempted on basal MS medium containing different concentration of sucrose or mannitol. Highest maturation frequency of PLBs was observed on medium containing 261 mM sucrose. PLBs matured on medium containing 261 mM sucrose were used for conversion on MS medium variously supplemented with BAP and GA3. It was interesting to note that PLBs matured on 261 mM sucrose and 247 mM mannitol concentration showed 81.207% and 78.127% germination respectively after 30 days of culture. Matured PLBs (on 261 mM sucrose) were encapsulated into sodium alginate gels to produce synthetic. The storage of synthetic seeds was studied at 25ºC and 4ºC. The synthetic seeds stored at 4ºC were viable for longer period as compared to those stored at 25ºC. Higher conversion frequency was also observed in PLBs stored at 4ºC.
Keywords: Cymbidium giganteum; Cymbidium elegans; Micropropagation; Maturation; Conversion; PLBs; Synthetic seeds